2023
DOI: 10.1109/jphot.2023.3248660
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-High Quality Factor Resonances in a Pinwheel-Shaped All-Dielectric Metasurface Based on Bound States in the Continuum

Abstract: Combining with the bound states in the continuum (BICs) theory in all-dielectric metasurfaces has become an extensively used method to excite multiple high quality(Q) factor Fano resonances, which remarkably enhance the performance of structures to be applied to refractive index sensors. In this paper, a novel silicon pinwheel-shaped all-dielectric metasurface in the near-infrared region is designed and numerically investigated. Two Fano resonances are excited in the original structures. After breaking the sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…To evaluate the performance of refractive index sensor, the two main performance indicators which include the sensitivity ( S ) and the figure of merit ( FOM ) are analyzed. Here, S is given by [ 17 ]: where is the offset of resonant wavelength and is the variation of refractive index. The FOM can be obtained using [ 17 ]: Where FWHM represents the full-width at half-maximum of Fano resonance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate the performance of refractive index sensor, the two main performance indicators which include the sensitivity ( S ) and the figure of merit ( FOM ) are analyzed. Here, S is given by [ 17 ]: where is the offset of resonant wavelength and is the variation of refractive index. The FOM can be obtained using [ 17 ]: Where FWHM represents the full-width at half-maximum of Fano resonance.…”
Section: Resultsmentioning
confidence: 99%
“…Here, S is given by [ 17 ]: where is the offset of resonant wavelength and is the variation of refractive index. The FOM can be obtained using [ 17 ]: Where FWHM represents the full-width at half-maximum of Fano resonance.…”
Section: Resultsmentioning
confidence: 99%
“…431 (Sim.) Bound states in the continuum 29) 2023 the symmetry of metasurfaces, we find that the FOM of the hollow Mie resonators based on the non-radiative TMD mode is as high as 1389 RIU −1 , which is 92 times greater than that of the MD mode-based metasurfaces (15 RIU −1 ). The FOM of the proposed hollow Mie resonators is also greater than that of the BIC-based metasurfaces.…”
mentioning
confidence: 86%
“…Moreover, the geometric shapes of chiral metasurfaces can be arbitrarily controlled, and their optical responses can be tailored by adjusting the structural parameters of the chiral metamaterial. This presents a wide range of applications in various fields, indicating promising prospects for the development of chiral metasurfaces [9][10]. In 2023, Hwaseob Lee demonstrated that a Mie-resonant metamaterial resonator, composed of a symmetrical and asymmetrical Mie scatterer pair, could reach exceptional points or chosen chirality while efficiently suppressing backscattering [11].…”
Section: ⅰIntroductionmentioning
confidence: 99%